Contração de polimerização e expansão higroscópica de resinas compostas: análise pela técnica de video-imagem - Borges, Alexandre Luiz Souto [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
To evaluate the volumetric changes due to polymerization and thermocycling on different resin-composites. Methods: Thirteen A2 Universal Dentin shade resin-composites (n = 10) from eight manufacturers were evaluated (4Seasons, Grandio, Venus, Amelogen Plus, P90, Z350, Esthet-X, Amaris, Vita-l-escence, Natural-Look, Charisma, Z250 and Opallis). The polymerization shrinkage percentage (PS) was calculated using an image measurement device (ACUVOL - Bisco Dental). Equal volumes of material, standardized by a semisphere polyurethane matrix (d = 3mm) were used and, after 5 minutes of relaxation, the baseline volume measurements were obtained with 18 J of energy dose from the LED light-curing unit. Measurements were obtained after 5 minutes and PS values calculated. Specimens were stored in a drydark environment for 24 hours and re-measured. Specimens were then thermocycled in distilled water between 5oC and 55oC for 20,000 cycles, subjected to another volume measurement at 5,000 cycle intervals. Specimens were gently dried prior to each measurement. Results: Repeated measurements were made using ANOVA (α = 0.05) showed that all resin-composite volumes were influenced by the number of cycles. Volumes at 5 minutes post-polymerization (12.47 ± 0.08) were significantly lower than those at baseline (12.80 ± 0.09). Volumes at 24 hours (12.43 ± 0.19) were insignificantly lower than those at 5 minutes postpolymerization. With regards to the impact of thermocycling, all specimens showed statistically significant increases in volume after 5,000 cycles (13.04 ± 0.22). Although statistically different from those after 5,000 cycles, there was no statistically significant difference between volumes measured at 10,000 (12.87±0.21), 15,000 (12.92±0.24), and 20,000 (12.84±0.23) cycles. Conclusion: According to the video-imaging analysis, thermocycling caused a significant expansion in resin-composites tested, the volume increase was not able to...

O presente estudo teve como finalidade avaliar a contração de polimerização e o efeito volumétrico da sorção de água (expansão higroscópica), por meio do aumento de volume, registrado pela técnica de video-imagem. Métodos: Treze tipos de resinas compostas (n=10) de 8 fabricantes com diferentes características físicas, tipos e quantidade de carga, viscosidade, polímeros constituintes e aplicação clínica com cor A2 para dentina (4Seasons, Grandio, Venus, Amelogen Plus, P90, Z350, Esthet-X, Amaris, Vita-l-escence, Natural-Look, Charisma, Z250 and Opallis), foram avalidos. A porcentagem de contração de polimerização foi calculada usando um aparelho de video-imagem (ACUVOL - Bisco Dental), onde volumes iguais foram padronizados usando uma matriz de poliuretano em forma de calota com 3mm de diâmetro e 2mm de altura e após 5 minutos de descanso no pedestal do aparelho o volume inicial da massa foi medido e calculado para servir como valor inicial (baseline) e 18J de energia fornecidos a massa por meio de uma unidade de luz LED para fotopolimerização e assim calcular o valor da contração de polimerização de cada resina. Os espécimes então foram armazenados em ambiente seco e com ausência de luz e após 24 horas medidos novamente para verificação do novo volume inicial. A partir deste dados todos os espécimes foram termociclados em uma sequencia de 5.000, 10.000, 15.000 e 20.000 ciclos completos em água destilada a 5°C e 55°C. Ao final de cada marcação os corpos de prova foram secos com um leve jato de ar por 15s e levados novamente à máquina de medição, para compararmos com o volume final. Resultados: O teste ANOVA uma fator para medidas repetidas (α = 0.05) foi aplicado e mostrou que todas as resinas tiveram o volume influenciado pelo número de ciclos térmicos. Os volumes após 5 minutos da polimerização (12,47 ± 0,08) foi significantemente menor que o da porção total inicial...
Keywords: Resinas compostas; Polimerização; Método dos elementos finitos; Materiais dentários; Composite resins